Paths shared between people (Homo sapiens sapiens) and dogs (Canis familiaris): from aid therapy partners to friends and family members (Acta Scientiarum. Human and Social Sciences, 2024)
Dogs (Canis familiaris) were the first domesticated species and today, they still have a central role in our societies. Integrated in the post-humanistic approach, we aimed to understand the evolution of the different social roles assumed by dogs, specifically, aid therapy dogs (ATD) that warn human diabetics of the changes that occur in their blood glycemia.  Our main objective was to see if at some point in these shared paths, ATD would start being seen in a different way by their tutors and families. Specifically, we looked for: i) Exploring according to the perceptions of the tutors and family members (FM) how an ATD can improve the wellbeing and quality of life of diabetics (both dogs, and humans with diabetes were part of a medical association named Associação Pata d’Açúcar – Medical Dogs for Diabeties (from now onwards Pata d’Açúcar) on which dogs are trained to be ATD to latter be attributed to patients with diabetics and ii) To understand how ATD may occupy different roles throughout the time: from ATD to companion animals (CA) or even family members (FM). Our methodological approach was a qualitative one, centred in observation and semi-structures interviews applied to patients from Pata d’Açúcar. All Humans that accepted to be part for this study were interviewed and observed in different phases of shared coexistence with ATD’s: those who lived with an ATD for more than 5 years, more than 2 years and finally, just for a few months. Our sample was probabilistic and stratified. The main conclusion of our study is that for most of the interviewees, ATD’s started to being CA and simultaneously FM. Furthermore, ATD’s did also work as true ice-breakers in the case of children with difficulties in socializing with peers, facilitating the interactions between individuals of the same or similar age groups.